Multiparametric detection and outcome prediction of pancreatic cancer involving dual-energy CT, diffusion-weighted MRI, and radiomics - Koch, Vitali; Weitzer, Nils; Dos Santos, Daniel Pinto; Gruenewald, Leon D.; Mahmoudi, Scherwin; Martin, Simon S.; Eichler, Katrin; Bernatz, Simon; Gruber-Rouh, Tatjana; Booz, Christian; Hammerstingl, Renate M.; Biciusca, Teodora; et al. (Cancer imaging, 2023)
The advent of next-generation computed tomography (CT)- and magnetic resonance imaging (MRI) opened many new perspectives in the evaluation of tumor characteristics. An increasing body of evidence suggests the incorporation of quantitative imaging biomarkers into clinical decision-making to provide mineable tissue information. The present study sought to evaluate the diagnostic and predictive value of a multiparametric approach involving radiomics texture analysis, dual-energy CT-derived iodine concentration (DECT-IC), and diffusion-weighted MRI (DWI) in participants with histologically proven pancreatic cancer.
Gesehen am 01.08.2023